Cost Analysis of Flexible Pavement Construction at Polinela Campus Based on AHSP Bina Marga 2025: Analisis Biaya Pekerjaan Jalan Lentur di Kampus Polinela dengan AHSP Bina Marga 2025 - Resti Agustina; Titi Ariyanti; Mira Wisman; Andy Eka Saputra; Rahayu Putri Amalia (Universitas Nahdlatul Ulama Blitar, 2026)
Politeknik Negeri Lampung (POLINELA) covers a total area of 29.41 hectares, with functional buildings distributed across the campus. This spatial distribution necessitates the use of vehicles for inter-building mobility. Consequently, high-quality internal road infrastructure is critical to ensuring efficient travel times and distances, supporting both academic and operational activities. This study aims to analyze the estimated cost of implementing flexible pavement construction on the internal road network of the POLINELA campus. The analysis was conducted by developing a cost estimate (RAB) based on the 2025 Analysis of Work Unit Prices (AHSP) issued by the Directorate General of Bina Marga. The unit price standards were referenced from the 2025 Price Schedule of Bandar Lampung City. The research methodology involved calculating work volumes, determining the AHSP, and summarizing the total project cost. The scope of work includes mobilization, land surveying (stake-out), common excavation, embankment, subgrade preparation, Aggregate Base Class A and Class B, prime coat, tack coat, and Asphalt Concrete-Wearing Course (AC-WC) surfacing. The calculation results indicate that the total estimated cost for the flexible pavement construction at the POLINELA campus is Rp4,472,800,000.00 (four billion four hundred seventy-two million eight hundred thousand rupiahs).